Role of Matrix Metalloproteinases in Angiogenesis and Cancer - Quintero-Fabián, Saray; Arreola, Rodrigo; Becerril-Villanueva, Enrique; Torres-Romero, Julio César; Arana-Argáez, Victor; Lara-Riegos, Julio; Ramírez-Camacho, Mario Alberto; Alvarez-Sánchez, María Elizbeth (Frontiers in Oncology, 2019)
During angiogenesis, new vessels emerge from existing endothelial lined vessels to promote the degradation of the vascular basement membrane and remodel the extracellular matrix (ECM), followed by endothelial cell migration and proliferation and the new generation of matrix components. Matrix metalloproteinases (MMPs) participate in the disruption, tumor neovascularization, and subsequent metastasis while tissue inhibitors of metalloproteinases (TIMPs) downregulate the activity of these MMPs. Then, the angiogenic response can be directly or indirectly mediated by MMPs through the modulation of the balance between pro- and anti-angiogenic factors. This review analyzes recent knowledge on MMPs and their participation in angiogenesis.